Risk Factors for Ramp Lesions of the Medial Meniscus: A Systematic Review and Meta-analysis. Issue 13 (November 2021) - Kunze, Kyle N.; Wright-Chisem, Joshua; Polce, Evan M.; DePhillipo, Nicholas N.; LaPrade, Robert F.; Chahla, Jorge
Background: Failure to appropriately identify and repair medial meniscal ramp lesions at the time of anterior cruciate ligament (ACL) reconstruction (ACLR) may result in increased anterior tibial translation and internal rotation, increasing the risk for graft failure. Knowledge of the risk factors leading to the development of ramp lesions may enhance clinicians' vigilance in specific ACL-deficient populations and subsequently repair of these lesions at the time of ACLR. Purpose: To perform a systematic review and meta-analysis of factors tested for associations with ramp lesions and to determine which were significantly associated with the presence of ramp lesions. Study Design: Systematic review and meta-analysis; Level of evidence, 4. Methods: PubMed, OVID/Medline, and Cochrane databases were queried in April 2020. Data pertaining to study characteristics and reported risk factors for ramp lesions were recorded. DerSimonian-Laird binary random-effects models were constructed to quantitatively evaluate the association between risk factors and ramp lesions by generating effect estimates in the form of odds ratios (ORs) with 95% CIs. Qualitative analysis was performed to describe risk factors that were variably reported. Results: The review included 12 studies with 8410 patients. The overall pooled prevalence of ramp lesions was 21.9% (range, 9.0%-41.7%). A total of 45 risk factors were identified, of which 8 were explored quantitatively. There was strong evidence to support that posteromedial tibial edema on magnetic resonance imaging (MRI) (OR, 2.12; 95% CI, 1.27-3.56; P = .004), age <30 years (OR, 2.02; 95% CI, 1.23-3.22; P = .002), and complete ACL tears (OR, 3.0; 95% CI, 1.41-6.20; P = .004) were risk factors for ramp lesions. There was moderate evidence to support that male sex (OR, 1.58; 95% CI, 1.36-1.83; P < .001) and concomitant lateral meniscal tears (OR, 1.54; 95% CI, 1.11-2.13; P = .009) were risk factors for ramp lesions. Chronic ACL injury (≥24 months) demonstrated minimal evidence as a risk factor (OR, 1.41; 95% CI, 1.14-1.74; P = .001). No significant associations were determined between contact injury or revision ACLR and the presence of ramp lesions. Conclusion: Significant associations between male sex, age <30 years, posteromedial tibial edema on MRI, concomitant lateral meniscal tears, complete ACL tears, injury chronicity, and the presence of ramp lesions were found. Contact injury and revision ACLR were not significantly associated with the presence of ramp lesions.